PENGARUH FINANCIAL DISTRESS, PERGANTIAN MANAJEMEN, PERTUMBUHAN PERUSAHAAN DAN OPINI AUDIT TERHADAP PERGANTIAN AUDITOR PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011-2013 - Gustha Priyatna; Hadi Pramono (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2015)
This research aimed at examining the impact of financial distress, management switching, company growth and audit opinion toward auditor switching. Financial distress was measured by dummy, if a company had more than 100% DER ratio, it would be given 1 point and one with less than 100% DER ratio would given 0 point. Company growth was measured by using company selling. Audit opinion was measured by using dummy, if client company received unqualifed opinion report with explanatory language, qualifed opinion report, adverse opinion report and disclaimer of opinion report would be given 1 point and company with unqualifed opinion report would be given 0 point. The sample of this research was manufacturing company listed in Indonesian busary effect in 2011-2013. For taking the data, the researcher apllied purposive sampling which result 69 companies. The analysis method used was logistic regression. The hypothesis result showed that financial distress and management switching didn’t give any positive effects toward the auditor switching. While the company growth and audit opinion didn’t give any negative effects toward auditor switching.Keywords: auditor switching, financial distress, management switching, company growth, audit opinion.